A rare homozygous missense GDF2 (BMP9) mutation causing PAH in siblings: Does BMP10 status contribute?. Issue 1 (19th October 2022) - Upton, Paul; Richards, Susan; Bates, Angela; Niederhoffer, Karen Y.; Morrell, Nicholas W.; Christian, Susan
Abstract: Pulmonary arterial hypertension (PAH) is a disease characterized by pathological remodeling of the pulmonary vasculature causing elevated pulmonary artery pressures and ultimately, right ventricular failure from chronic pressure overload. Heterozygous pathogenic GDF2 (encoding bone morphogenetic protein 9 (BMP9)) variants account for some (>1%) adult PAH cases. Only three pediatric PAH cases, harboring homozygous or compound heterozygous variants, are reported to date. Ultra‐rare pathogenic GDF2 variants are reported in hereditary hemorrhagic telangiectasia and overlapping disorders characterized by telangiectasias and arteriovenous malformations (AVMs). Here, we present two siblings with PAH homozygous for a GDF2 mutation that impairs BMP9 proprotein processing and reduces growth factor domain availability. We confirm an absence of measurable plasma BMP9 whereas BMP10 levels are detectable and serum‐dependent endothelial BMP activity is evident. This contrasts with the absence of activity which we reported in two children with homozygous pathogenic GDF2 nonsense variants, one with PAH and one with pulmonary AVMs, both with telangiectasias, suggesting loss of BMP10 and endothelial BMP activity in the latter may precipitate telangiectasia development. An absence of phenotype in related heterozygous GDF2 variant carriers suggests incomplete penetrance in PAH and AVM‐related diseases, indicating that additional somatic and/or genetic modifiers may be necessary for disease precipitation.